CHINESE PESANTREN AND CHINA’S ACCEPTANCE TO ISLAM A STUDY ON COUNSELING SPIRIT IN CHINESE PESANTREN HU DENGZHOU JINGTANG JIAOYU - Moh Khoerul Anwar; Nur Musyafak; Zaen Musyrifin (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
Counseling is a psychological service provided by people who have the skills to listen well, the skills to understand others, and the skills to humanize people. These three spirits are done by one Islamic figure who teaches about Islamic culture in China to establish a pesantren (Jingtang Jiaoyu in Chinese) that has now increased. Hu Dengzhou is the early figure of Islamic education in China, and some concept developed by it is part of counseling. The idea applied is a) psychological services are given classically for people who need peace and peacefulness b) service processes are given gradually according to the assessment, if viewed from the aspect of counseling With the services provided in accordance with the results of the need assessment, c) individual counseling supplied for each student, as well as the teacher (Kyai in Indonesia) that accompanies each Student (Santri in Indonesia) so as to understand the characters, behaviors, personalities, and skills about student. The conclusion of this article is the spirit of counseling has existed since ancient times and has applied to pesantren based on Islamic culture, especially in China. Then Islam in China is not problematic because the Chinese government also recognizes that Islam is part of a culture that has existed since ancient times.